Dynamic modelling of local fuel inventory and desorption in the whole tokamak vacuum vessel for auto-consistent plasma-wall interaction simulations. (May 2019) - Denis, J.; Bucalossi, J.; Ciraolo, G.; Hodille, E.A.; Pégourié, B.; Bufferand, H.; Grisolia, C.; Loarer, T.; Marandet, Y.; Serre, E.; ,
Highlights: A model to simulate the dynamic thermal desorption of hydrogen isotopes is built for the SolEdge2D-EIRENE code package. This model is used for simulating a sequence of plasma pulses to study the wall dynamic retention. The vacuum vessel pressure obtained from the simulated outgassing rate after a pulse is compared to experimental pressure measurement. The pressure drop is qualitatively well reproduced with a ∼ t −0.8 trend. Retention rate during the plasma pulses is studied. Abstract: An extension of the SolEdge2D-EIRENE code package, named D-WEE, has been developed to add the dynamics of thermal desorption of hydrogen isotopes from the surface of plasma facing materials. To achieve this purpose, D-WEE models hydrogen isotopes implantation, transport and retention in those materials. Before launching auto-consistent simulation (with feedback of D-WEE on SolEdge2D-EIRENE), D-WEE has to be initialised to ensure a realistic wall behaviour in terms of dynamics (pumping or fuelling areas) and fuel content. A methodology based on modelling is introduced to perform such initialisation. A synthetic plasma pulse is built from consecutive SolEdge2D-EIRENE simulations. This synthetic pulse is used as a plasma background for the D-WEE module. A sequence of plasma pulses is simulated with D-WEE to model a tokamak operation. This simulation enables to extract at a desired time during a pulse the local fuel inventory and the local desorption flux density which could be used as initial condition for coupled plasma-wall simulations. To assess the relevance of the dynamic retention behaviour obtained in the simulation, a confrontation to post-pulse experimental pressure measurement is performed. Such confrontation reveals a qualitative agreement between the temporal pressure drop obtained in the simulation and the one observed experimentally. The simulated dynamic retention during the consecutive pulses is also studied.